O ensino da trigonometria no triângulo retângulo - Sangali, Muriel Belique (2021)
The main objective of this work is to present a proposal for teaching the trigonometric ratios sine, cosine and tangent. The investigative and meaningful approach is aimed at students from the 9th grade of elementary school and the 2nd grade of high school. To strengthen the concepts and activities, we will use Geogebra dynamic geometry software. The study presents a brief approach to the history of trigonometry in order to explore the study of trigonometric ratios applied to contextualized and practical problems.